Government's Responsibilities and Citizens' Duties in a Democratic System: The implication for Nigerian Fourth Republic - Tom, Tom (Journal of International Relations, 2021)
In any political system the presence of government and citizens is sine qua non. In keeping with the purpose for which government was established, citizens expect government not only to be responsible for all its actions towards them, but also be responsive to their yearning just as government expects its citizens to discharge their duties to the state. It is often claimed that democracy is a system of government that enables both the leaders and the citizens to be conscious of what is required, and accomplish it for the betterment of the society in terms of political, social and economic development. In Nigeria, it is argued, however, that neither government nor the citizens have discharged their statutory functions satisfactorily. The study was undertaken to examine the extent to which the Nigerian state and its citizens have lived up to their statutory and civic requirements. The study revealed that most citizens of Nigeria are politically docile, gullible, and parochial. This has led to a situation where citizen"˜ rights are trampled upon and made them easy target of elites"˜ maneuvers. The citizens"˜ level of political awareness and participation is low and this has resulted in the being shirking of their duties to the state. The work is of the view that democratic system in Nigeria could only be sustained when both the state and its citizens accept their duties and responsibilities as being inherent and inalienable. Both descriptive and historical methods were used in the study. It recommended among others that government should work to help citizens through massive education to develop their capacity for democratic participations and civic leadership.